Perbedaan Prestasi Belajar ditinjau dari Sociometric Status di SMPN 1 Bangli - Batuh, A.A. Gede Raka Narayana; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana; Vol 3 No 2 (2016)DO - 10.24843/JPU.2016.v03.i02.p12, 2016)
Slameto (2003) explains that one of the factors that influence learning achievement is a relation peers or position of the student relationship with friends around. The position of the student relationship with a friend in the class can be described by Sociometrics Status. Sociometric status means a reflection of the general acceptance of individuals by peers (Finch, 1998) The purpose of this study was to determine differences in learning achievement in terms of sociometric status in SMPN 1 Bangli. This research is a mixed-method. The sampling technique used was cluster random sampling. Subjects in this study amounted to 189 students who attend school at SMPN 1 Bangli. Data mining techniques used in this study begins with interviews and the interviews made in the questionnaire and subsequent sociometric status sociometric status questionnaire distributed to the study subjects. Data were analyzed using the Kruskal-Wallis test. Based on the results of data analysis, showed that there is a significant difference in learning achievement in terms of sociometric status in SMPN 1 Bangli. If students want to get high academic achievement, the students can improve their relationships with friends around. Keyword: Learning Achievement, Sociometric Status.